1999
DOI: 10.1123/apaq.16.4.403
|View full text |Cite
|
Sign up to set email alerts
|

Motor Proficiency of Boys with Attention Deficit Hyperactivity Disorder and Boys with Learning Disabilities

Abstract: The motor proficiency of 56 boys with attention deficit hyperactivity disorder (ADHD) was compared with that of 56 boys with learning disabilities (LD); both groups were divided into two age groups, 7 to 8 years and 9 to 12 years. Boys with ADHD were taking Ritalin and attending public schools. Boys with LD were medication-free and attending private schools for LD. The Bruininks-Oseretsky Test of Motor Proficiency–Long Form (BOTMP–LF) was used to measure balance, bilateral coordination, strength, upper limb co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
1
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 39 publications
3
23
1
3
Order By: Relevance
“…Findings were consistent with previous studies by Harvey et al (2007), Berkeley et al (2001), Dewey et al (2007), Beyer (1999), and others that have reported that children with ASD and ADHD performed poorly in their motor skills as compared with typically developing children. It is important to note, however, that not all children diagnosed with ASD or ADHD displayed motor difficulties.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Findings were consistent with previous studies by Harvey et al (2007), Berkeley et al (2001), Dewey et al (2007), Beyer (1999), and others that have reported that children with ASD and ADHD performed poorly in their motor skills as compared with typically developing children. It is important to note, however, that not all children diagnosed with ASD or ADHD displayed motor difficulties.…”
Section: Discussionsupporting
confidence: 93%
“…They found that three groups of children were significantly impaired on motor coordination skills, but only children with ASD showed a generalized impairment in gestural performance. Beyer (1999) compared the motor proficiency of boys with ADHD and boys with LD using the BOTMP-Long Form, and found significantly poorer performance for boys with ADHD than boys with LD on all variables except balance, upper limb coordination, and response speed.…”
Section: Introductionmentioning
confidence: 98%
“…Παρόμοια κινητικά προβλήματα παρουσιάζουν και τα παιδιά με σύνδρομο διαταραχής προσοχής/υπερκινητικότητας, τα οποία μάλιστα υστερούν όχι μόνο σε σχέση με τα παιδιά τυπικού πληθυσμού αλλά και με τα παιδιά με μαθησιακές δυσκολίες (Beyer, 1999), παρουσιάζοντας χαμηλή απόδοση στις λεπτές κυρίως κινητικές δεξιότητες (Whitmont & Clark, 1996).…”
Section: ιαταραχή προσοχής-υπερκινητικότηταunclassified
“…Ανασκόπηση βιβλιογραφίας 64 ισορροπίας (Cinelli & De Paepe, 1984), συναρμογής (Kendrick & Hanten, 1980) και ταχύτητας αντίδρασης (Beyer, 1999 (Reeves, 1998).…”
Section: αποκλίσεις στην κινητική ανάπτυξηunclassified
See 1 more Smart Citation